2002
DOI: 10.1096/fj.02-0142fje
|View full text |Cite
|
Sign up to set email alerts
|

3 H‐thymidine is a defective tool with which to measure rates of DNA synthesis

Abstract: Metabolic incorporation of 3H-thymidine into cellular DNA is a widely used protocol to monitor rates of DNA synthesis and cell proliferation. However, this radiochemical has also been reported to induce cell-cycle arrest and apoptosis in addition to DNA damage. Using stable isotope-labeled thymidine, we demonstrate that 3H-thymidine induces dose-dependent inhibition of the rate of DNA synthesis. This inhibition occurred within the first round of replication after addition of the radiolabeled tracer and demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 21 publications
2
77
0
2
Order By: Relevance
“…Thus, in a recent study beryllium sensitization has been determined by a FACS lymphocyte proliferation test, which gave results comparable to the conventional BeLTT [23]. Recently, a method based on mass spectrometric detection on [ 13 C, 15 N]-labeled thymidine has also been reported for measuring the rate of DNA synthesis [24].…”
Section: Or Radiolabeled [mentioning
confidence: 98%
“…Thus, in a recent study beryllium sensitization has been determined by a FACS lymphocyte proliferation test, which gave results comparable to the conventional BeLTT [23]. Recently, a method based on mass spectrometric detection on [ 13 C, 15 N]-labeled thymidine has also been reported for measuring the rate of DNA synthesis [24].…”
Section: Or Radiolabeled [mentioning
confidence: 98%
“…While such methods provide information concerning the capability of these proteins to be phosphorylated during the actual time period of radiolabeling, they do not identify proteins already phosphorylated to significant levels prior to the labeling step. In addition, metabolically incorporating radiolabels, using standard doses and time courses, have previously been shown to induce DNA fragmentation, elevate p53 tumor suppressor protein levels, alter cell/ nuclear morphology, and result in cell cycle arrest or apoptosis (11)(12)(13)(14). Unlike radiolabeling, Western blotting potentially identifies all the phosphorylated proteins in samples (2, 8).…”
mentioning
confidence: 99%
“…The authors observed a dose dependent decrease in smooth muscle cell proliferation in vitro with crosslinked coacervated α-elastin, suggesting a potential reduction of intimal hyperplasia in vivo (Ito et al, 1998a). The authors repeated the study using tritiated thymidine to monitor cell proliferation and despite evidence suggesting that tritiated thymidine may result in cell arrest and apoptosis (Hu et al, 2002), the authors reported increased endothelial cell proliferation at a coacervated α-elastin concentration of 0.1 mg/mL (Ito et al, 1998b).…”
Section: Vascular Prostheses Passivationmentioning
confidence: 99%